Rhizophora Spp. And Epoxy Resin Based Semi-Anthropomorphic Liver Phantom For Lesions Enhancement In Computed Tomography - Al-Shipli, Marwan Ahmed Mostafa (2019)
This study aims to construct a semi-anthropomorphic liver phantom for the purpose of investigating image post-processing techniques to improve the visibility of liver lesions on images scanned at various computed tomography (CT) protocols. Rhizophora spp. particleboards and epoxy resin were evaluated to be used as basic materials, which construct a liver phantom with 16 cylindrical liver lesions.